(untitled) (European Journal of Child Development, Education and Psychopathology, 2024)
The main objectives of the study were 1) to analyze the relationship between physical activity and creativity in students aged 10-12 years, and 2) to measure the creativity outcomes of a game-based intervention program according to the level of physical activity of the participants. A game intervention program was carried out and the CREA and PAQ-C tests were done before (PRE) and after (POST) the intervention program. The results showed that after the game-based program, all students improved their creativity results with the CREA test (p < 0.01, TE = 0.6 to 1.3, moderate to large). However, no significant correlations (p > 0.05) were obtained between physical activity and creativity. Furthermore, no significant differences (p > 0.05) were found in the creativity according to the level of physical activity of the children. In conclusion, the present study shows that games are an effective way to improve creativity of boys and girls between 10 and 12 years old, and that there are no differences between the effect of games on creativity between boys and girls who have a medium-low and medium-high level of physical activity.